2020
DOI: 10.1080/21691401.2020.1725533
|View full text |Cite
|
Sign up to set email alerts
|

Silencing MEG3 protects PC12 cells from hypoxic injury by targeting miR-21

Abstract: Increasing number of literatures highlighted lncRNA maternally expressed gene 3 (MEG3) as an emerging target for hypoxic-ischaemic brain damage (HIBD). This study attempted to assess the role of MEG3 in a cell model of HIBD. Expression of MEG3 in PC12 cells was suppressed by siRNA-mediated transfection, after which the cells were subjected to hypoxia. Cell viability, apoptosis, migration and the expression of related proteins were assessed. Furthermore, the downstream gene of MEG3 and its downstream signalling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In terms of the role of ceRNA, lncRNA MEG3 can bind different miRNAs like a "sponge" and contribute to the regulatory network of miRNAs. For example, the neuroprotective effect of MEG3 silencing on PC12 cells is through the regulation of PI3K/AKT and NF-kB pathways by sponging miR-21 [44]. Likewise, another study showed that down-expression of MEG3 could promote the proliferation of colonic stem cells in early colorectal cancer through binding miR-708 [45].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the role of ceRNA, lncRNA MEG3 can bind different miRNAs like a "sponge" and contribute to the regulatory network of miRNAs. For example, the neuroprotective effect of MEG3 silencing on PC12 cells is through the regulation of PI3K/AKT and NF-kB pathways by sponging miR-21 [44]. Likewise, another study showed that down-expression of MEG3 could promote the proliferation of colonic stem cells in early colorectal cancer through binding miR-708 [45].…”
Section: Discussionmentioning
confidence: 99%
“…It is of great significance for the management of related diseases to investigate the mechanism of ICC loss. Recently, MEG3 is reported to promote inflammation, apoptosis, and oxidative stress in various cells, while its known target miR-21 plays the opposite role [ 22 , 43–45 ]. However, their functions in ICC have not been revealed yet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that miR-21 can protect cell from oxidative stress and apoptosis [ 19–21 ]. Interestingly, increasing evidences show that miR-21 is negatively regulated by MEG3 in different types of tissues [ 22–24 ]. The interaction between MEG3 and miR-21 and their function in ICC have not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…To further emphasize the biological functions of MEG3, they also silenced the lcnRNA in a focal cerebral ischemia and reperfusion model induced by intraluminal MCAO. Indeed, they found that silencing MEG3 leads to protection against in vivo I/R-induced ischemic damage and improved overall neurological functions [95,96].…”
Section: Lncrna Meg3 In Hypoxic/anoxic Conditionsmentioning
confidence: 99%